Pengembangan Metode Analisis Sitrinin dan Upaya Penurunan Produksi Sitrinin dalam Fermentasi Cair Monascus purpureus - Jatmika, Catur; Wibowo, Marlia Singgih; Miftah, Amir Musadad (Pengurus Pusat Ikatan Apoteker Indonesia, 2023)
Citrinin, a fluorescent compound that contaminates a number of agricultural products, is a toxic compound especially to the kidneys and liver. This study aimed to develop analysis method for citrinin by HPLC and to reduce the level of citrinin in broth extract from Monascus purpureus fermentation microbiologically. The citrinin extraction method from fermentation broth was optimized by various pH and extracting solvents. The citrinin extract was incubated with Bacillus firmus bacteria at various growth phases. The levels of citrinin in the extract decreased significantly after incubating for 24 hours with the bacteria. Citrinin was analyzed HPLC by fluorescence detector at λexc 330 nm and λem 500 nm, mobile phase 0.033 M phosphoric acid: acetonitrile (1: 1), flow rate 1 mL/min with an average retention time of 6.1 minutes. The recovery was in the range of 78-83%. The precision method as shown by the coefficient of variance of 2.1%, with limit of detection and quantitation 0.03 µg/mL and 0.11 µg/mL respectively. Linearity was expressed by a correlation coefficient (r) of 0.9996 and a coefficient of variation of the regression function (Vx0) of 1.3%. The citrinin level in the extract was 0.69 µg/mL. The levels of citrinin after incubation with nutrient broth media contain bacterial culture aged 5 hours, 9 hours, and 14 hours were 0.56 ± 0.03, 0.27 ± 0.02, 0.26 ± 0.01, and 0.24 ± 0.01 µg/mL, respectively. Incubation of Bacillus firmus bacteria on citrinin extract significantly reduced the levels of citrinin in the extract.